WHEAT YIELD AND PHOSPHORUS USE EFFICIENCY AS INFLUENCED BY METHOD OF PHOSPHORUS AND ZINC APPLICATION (Biological Sciences - PJSIR, 2002)
Phosphatic  fertili zers  are  recom mended  to  be  applied  as broadcast a nd  incorporated  i nto  th e  soil  before  sowin g._ Mo_re recently application  of fertilizer with  irrigation water  as solution , termed  "Fertigation ", has been  found equally _effective for wheat  production . Fertilizer zinc whose requirement  i s small  and  is commonly deficient  in  soils, was tried  as _tert1gatt on  morder to determine its effect on yield and P use efficiency by wheat. Single superphosphate fertilizer was applied at 22 and 44 kg P ha·1 either ·alone or with 1O kg Zn  ha·1. The method  of application  employed was broadcast at sowing and   fert1gat10nat first  irrigation . It was found  that  rate  of P application  increa sed wheat  grain  yield  over control  and  P applied @_ 44 .kg  h a·1 by fertigation  proved  significan tly better than broadcast application. Addition of Zn as broadcast or as    fert1gat10nshowed no difference in yield compared to P alone. Application of Zn by fertigat,on , however, unproved agronomic and P fertil izer efficiency com pared to  its broadcast application at  sowing.